Insights Into the Load-Carrying Mechanism and Interactive Effects of Dissimilar Piles in Cushioned Piled Rafts - Uba Uge, Bantayehu; Guo, Yuancheng; Zhao, Jun; Liu, Yunlong; Mehmood, Mudassir; Lv, Chenyu; Xia, Yanyan (Civil Engineering Journal, 2025)
Disconnecting pile heads from the raft has gained wide application because the gravel and geogrid layers filling the space between them create a more even pressure distribution and reduce differential settlement. However, due to the complexity of modelling the multiple interfaces in the superstructure-foundation-subsoil system, previous findings on load-transfer mechanisms, interaction effects, and group optimization remain incomplete. Moreover, the common analytical approach employed for understanding the load transfer mechanism is the “unit cell’ concept, which cannot fully capture dissimilarity in the group. To address these limitations, this study aims to develop an analytical framework for predicting the load-settlement response of cushioned piled rafts with dissimilar piles. The proposed method simplifies the cushion-pile-soil interaction using a Winkler-type Spring model, while a hyperbolic load-transfer function captures the nonlinear pile-soil behavior. The model was verified against existing experimental and showed close agreement. It successfully captured the load-sharing mechanism, confirming that stiffer, longer, or larger-diameter piles attract a disproportionately higher share of the load. The novelty of this work lies in the establishment of an analytical model based on the principles of dissimilar pile groups but extended to include cushion force transmission, a critical integration that provides a realistic tool for practice.